Pitfalls in the Diagnosis of Anaplastic Large Cell Lymphoma with a Small Cell Pattern - Rowan L. Grigoropoulos; Penny Wright; Mars B. van t'Veer; Mike A. Scott; George A. Follows (Case Reports in Hematology)
Anaplastic large cell lymphoma with a small cell pattern is a rare T-cell lymphoma. This condition is more frequently seen in younger patients and should be considered when patients present with leucocytosis and constitutional symptoms. In this report, we describe our diagnostic work-up for one such case using blood, lymph node, and bone marrow aspirate samples, highlighting the variability of antigen expression seen in different sample types and methodologies. This case shows the importance of having a high index of suspicion and assessing CD30 and anaplastic lymphoma kinase expression in all suspected T-cell neoplasms even though this rare condition is not necessarily expected.